Simulation of the soil water content under different water deficits for apple trees via improved WOFOST-HYDRUS coupled model - Zhao, Long; Zhang, Haoran; Zhao, Xinbo; Ding, Yuehua; Shi, Yi; Cui, Ningbo; Qiu, Zhaomei (International Journal of Agricultural and Biological Engineering, 2025)
As a crucial fruit tree crop, the health and yield of apple trees are intricately linked to soil moisture conditions. Thisstudy aimed to integrate the enhanced WOFOST model with the HYDRUS model to simulate the growth and development ofapple trees, as well as the dynamics of soil moisture under varying degrees of water deficit. The outputs of evapotranspiration(ET0) and leaf area index (LAI) from the WOFOST model during the apple growth phase were specifically integrated withHYDRUS-1D. These parameters served as intermediaries to assess the impact of different water deficit scenarios on apple treegrowth and soil moisture content. The experimental design included three levels of water deficit treatments in addition tocontrol, with irrigation volumes for the deficit treatments set at 85%, 70%, and 55% of the control’s volume, respectively. Themodel-predicted LAI across all irrigation treatments exhibited an R2 range of 0.89-0.95, a normalized root mean square error(NRMSE) between 8.02% and 14.57%, and yield prediction errors ranging from 6.27% to 9.61%, closely aligned withempirical data. The accuracy of simulated soil moisture content was enhanced in the 0-30 cm layer, with a slight decrease inaccuracy observed in the 30-60 cm layer. For each irrigation treatment, the R2 values for simulated soil moisture content rangedfrom 0.77 to 0.89 in the 0-30 cm layer and from 0.75 to 0.81 in the 30-60 cm layer. This study validated the capability of theWOFOST-HYDRUS model to accurately simulate the effects of varied water deficit treatments on soil moisture, LAI, andapple tree yield, providing valuable insights for developing optimal irrigation strategies.Keywords: growth model, WOFOST-HYDRUS, apple trees, water simulation, water deficit treatmentDOI: 10.25165/j.ijabe.20251801.9384Citation: Zhao L, Zhang H R, Zhao X B, Ding Y H, Shi Y, Cui N B, et al. Simulation of the soil water content under different water deficits for apple trees via improved WOFOST-HYDRUS coupled model. Int J Agric & Biol Eng, 2025; 18(1): 219–229.